A new biomechanical glaucoma factor to discriminate normal eyes from normal pressure glaucoma eyes. Issue 7 (24th April 2019) - Pillunat, Karin R.; Herber, Robert; Spoerl, Eberhard; Erb, Carl; Pillunat, Lutz E.
Abstract: Background: To test the ability of the newly calculated Dresden biomechanical glaucoma factor (DBGF) based on dynamic corneal response (DCR) deformation and corneal thickness parameters, to discriminate between healthy and normal pressure glaucoma (NPG) eyes. Methods: Seventy healthy and 70 NPG patients of Caucasian origin were recruited for this multicentre cross‐sectional pilot study, which included both eyes for analysis. Logistic regression analysis with generalized estimating equation (GEE) models to account for correlations between eyes and a threefold cross‐validation were performed to determine the optimal combination of Corvis ST parameters in order to separate normal from NPG eyes. Results: The DBGF was calculated using 5 Corvis ST parameters, which showed the best discrimination power: deformation amplitude ratio progression, highest concavity time, pachymetry slope, the biomechanically corrected intraocular pressure and pachymetry. In a threefold cross‐validation, the receiver operating characteristic (ROC) curve confirmed an area under the curve (AUC) of 0.814 with a sensitivity of 76% and a specificity of 77% using a logit cut‐off value of a DBGF = 0.5. Conclusion: The DBGF shows to be sensitive and specific to discriminate healthy from NPG eyes. Since diagnosis of NPG is often challenging, the DBGF may help with the differential diagnosis of NPG in daily clinical practice. Therefore, it might be considered as a new possible screening method for NPG.